Ionophoretic Technique in the Study of Mixed Complexes [M(II)-Nitrilotriacetate-Valine System) - SINGH, SATYENDRA; GAUR, KANCHAN (Asian Journal of Chemistry, 2010)
Binary equilibria of M(II)-valine and also mixed complexes formation have been studied using paper electrophoresis. The log k values for mixed complexes have been found to be 5.24, 3.21 and 3.13 for Hg(II), Cd(II) and Mn(II) complexes respectively at μ= 0.1 and 35°C.